Leukocyte Count and Adverse Clinical Outcomes in Acute Ischemic Stroke Patients - Quan, Kehua; Wang, Anxin; Zhang, Xiaoli; Wang, Yongjun (Frontiers in Neurology, 2019)
Background: Post-ischemic inflammatory response might be affected by many factors. We chose leukocyte count as a marker of inflammatory response and investigated whether the predictive effects of leukocyte count on the clinical outcomes in acute ischemic stroke patients are different according to different factors. Methods: We derived data from the China National Stroke Registry II. Patients with ischemic stroke were classified into 4 groups by leukocyte count quartiles within the first 24 hours after admission. Adverse clinical outcomes were defined as recurrent stroke, all-cause death and poor functional outcomes (3≤mRS≤5) at 3-month and 1-year follow-up. The subgroup factors were age, sex, history of hypertension, history of diabetes, history of previous stroke or transient ischemic attack and smoking status. We assessed the association between leukocyte count and adverse clinical outcomes, and evaluated this association in different subgroups. Results: A total of 14,678 patients were included. Patients in higher quartiles were likely to be younger, male, smokers and drinker, and to have a shorter time from symptom onset to arrival, a more proportion of history of diabetes, atrial fibrillation and hypertension, and a higher severity of stroke. Higher quartiles were associated with elevated risk of adverse clinical outcomes at 3-month and 1-year follow-up. There was no difference in the relationship between leukocyte count and adverse clinical outcomes across subgroups such as age, sex, history of hypertension and smoking. The effect of leukocyte count on all-cause death was pronounced among patients with previous stroke or transient ischemic attack and the effect of leukocyte count on short-term poor functional outcomes was also pronounced among patients without diabetes. Conclusions: Leukocyte count is a simple and useful predictor for short-term and long-term clinical outcomes of acute ischemic stroke, especially in patients with certain specific characteristics.